Cerebral small vessel disease: Pathological mechanisms and potential therapeutic targets - Gao, Yue; Li, Di; Lin, Jianwen; Thomas, Aline M.; Miao, Jianyu; Chen, Dong; Li, Shen; Chu, Chengyan (Frontiers in Aging Neuroscience, 2022)
Cerebral small vessel disease (CSVD) represents a diverse cluster of cerebrovascular diseases primarily affecting small arteries, capillaries, arterioles and venules. The diagnosis of CSVD relies on the identification of small subcortical infarcts, lacunes, white matter hyperintensities, perivascular spaces, and microbleeds using neuroimaging. CSVD is observed in 25% of strokes worldwide and is the most common pathology of cognitive decline and dementia in the elderly. Still, due to the poor understanding of pathophysiology in CSVD, there is not an effective preventative or therapeutic approach for CSVD. The most widely accepted approach to CSVD treatment is to mitigate vascular risk factors and adopt a healthier lifestyle. Thus, a deeper understanding of pathogenesis may foster more specific therapies. Here, we review the underlying mechanisms of pathological characteristics in CSVD development, with a focus on endothelial dysfunction, blood-brain barrier impairment and white matter change. We also describe inflammation in CSVD, whose role in contributing to CSVD pathology is gaining interest. Finally, we update the current treatments and preventative measures of CSVD, as well as discuss potential targets and novel strategies for CSVD treatment.